Fibrillary Glomerulonephritis: An Update - Rosenstock, Jordan L. (Kidney Int Rep, 2019)
Fibrillary glomerulonephritis (FGN) is a rare proliferative form of glomerular disease characterized by randomly oriented fibrillar deposits with a mean diameter of 20 nm. By immunofluorescence (IF), the deposits stain for IgG, C3, and κ and λ light chains, suggesting that the fibrils may be composed of antigen-antibody immune complexes. A recent major advance in our understanding of the pathogenesis of FGN resulted from the discovery that a major component of the fibrils is DNA-J heat-shock protein family member B9 (DNAJB9), and immunohistochemical staining for DNAJB9 now makes it possible to diagnose FGN in the absence of ultrastructural evaluation. FGN has a poor prognosis, treatment options are currently limited, and transplant recurrence is not uncommon.